The role of multinational firms in the wage-gap debate - James R. Markusen; Anthony Venables (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
The observation of an increase in the ratio of skilled to unskilled wages in the high-income countries and in some cases in low/middle income countries has led to considerable discussion and indeed controversy as to its cause. Virtually none of the analysis has considered a possible role of multinational investment in explaining the wage gap phenomenon, despite the fact that direct investment surged during the late 1970's and 1980's, the same time in which the wage gap began to rise sharply in the US after years of decline. This paper adapts our earlier work to consider what role multinationals might play in factor markets. For a skilled-labor abundant country, we find that the wage gap may rise as countries become more similar in size and in relative endowments, and as investment is liberalized. However, falling trade costs may have the opposite effect on the wage gap, and the effect of grow in the world economy depends upon a number of initial conditions. Corresponding results are derived for initially unskilled-labor abundant countries.
Keywords: 330